النظام القانوني لتأديب القضاة في ضوء قانون السلطة القضائية الفلسطيني: دراسة تحليلية - بعلوشة, شريف أحمد (Revue jurisprudence; No 16 (2018): مجلة الاجتهاد القضائي, 2018)
بين قانون السلطة القضائية الفلسطينية رقم (1) لسنة 2002م الأحكام الوظيفية المتعلقة بالقضاة النظاميين، والمتمثلة في إجراءات تعيينهم ونقلهم وندبهم وإعارتهم، وحقوقهم وواجباتهم الوظيفية، وطريقة وإجراءات تأديبهم في حال إهمالهم أو إخلالهم بواجبات الوظيفة القضائية، ولقد تناولنا الأحكام المتعلقة بتأديب القضاة بالبحث والدراسة لبيان طبيعة النظام التأديبي الذي نهجه المشرع الفلسطيني في تأديب أعضاء السلطة القضائية، وإجراءات التحقيق معهم ومحاكمتهم تأديبياً، والضمانات التي منحهم إياها المشرع سواء أثناء التحقيق معهم، أو عند محاكمتهم وتوقيع العقوبة التأديبية عليهم، أو بعد صدور العقوبة بمنحهم حق التظلم من القرار التأديبي، أو الطعن فيه أمام المحكمة المختصة، وخلصنا لضرورة أخذ المشرع الفلسطيني بالنظام القضائي بجانب النظام الرئاسي في تأديب القاضي في حال كانت المخالفة التأديبية تستوجب عقوبة شديدة، وذلك بإحالة الموظف إلى المحكمة التأديبية لتتولى تأديبه وتوقيع الجزاء عليه، وقصر النظام الرئاسي على العقوبات المتعلقة بالتنبيه ولفت النظر فقط. الكلمات المفتاحية: السلطة القضائية، المخالفة التأديبية، تأديب القضاة، العقوبة التأديبية.   The Palestinian Judiciary Law No. (1) of 2002 showed the functional provisions relating to regular judges, that is presented in their recruitment, transfer, assignment, loan and their rights and duties, and the procedures of discipline in the case of neglect or breach of their duties of the judicial function. Also, we showed the provisions relating to the discipline of judges in research and study to demonstrate the nature of the disciplinary system used by the Palestinian legislator to discipline the members of the judiciary, and the procedures of investigation and disciplinary prosecution, and the guarantees conferred to them by the legislator whether during the investigation, trial or disciplinary punishment, or after the issuance of the sentence by granting them the right to appeal the disciplinary decision, or dispute him in front of the competent court. We concluded that the Palestinian legislator should apply the judicial system and the presidential system to discipline the judge if the disciplinary offense is punishable by severe punishment by referring the employee to the disciplinary court for disciplinary and punitive measures, and deficiency the presidential system sanctions alerting and drawing attention only. Keywords (judicial authority, disciplinary offense, discipline of judges, disciplinary punishment).